2019
DOI: 10.1016/j.jms.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Visible and ultraviolet laser spectroscopy of ThF

Abstract: The molecular ion ThF + is the species to be used in the next generation of search for the electron's Electric Dipole Moment (eEDM) at JILA. The measurement requires creating molecular ions in the eEDM sensitive state, the rovibronic ground state 3 ∆ 1 , v + = 0, J + = 1. Survey spectroscopy of neutral ThF is required to identify an appropriate intermediate state for a Resonance Enhanced Multi-Photon Ionization (REMPI) scheme that will create ions in the required state. We perform broadband survey spectroscopy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Sev- eral experiments in precision measurement 9,37 and cold chemistry 6,38 require molecular ions in a single quantum state, but typical methods of ion production (e.g., discharge, laser ablation) are violent and produce ions in numerous quantum states. In contrast, autoionization of Rydberg states has been used in a few previous experiments 8,9 to generate molecular ions in only a few quantum states, greatly increasing the yield of the desired state and reducing the complexity of subsequent state preparation steps. The calculated rotational state distributions presented here demonstrate that greater selectivity in the generation of single quantum state ions is possible by careful selection of high-Rydberg states as the precursor to autoionization.…”
Section: Rotational State Distributions From Autoionization Of G Rydb...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sev- eral experiments in precision measurement 9,37 and cold chemistry 6,38 require molecular ions in a single quantum state, but typical methods of ion production (e.g., discharge, laser ablation) are violent and produce ions in numerous quantum states. In contrast, autoionization of Rydberg states has been used in a few previous experiments 8,9 to generate molecular ions in only a few quantum states, greatly increasing the yield of the desired state and reducing the complexity of subsequent state preparation steps. The calculated rotational state distributions presented here demonstrate that greater selectivity in the generation of single quantum state ions is possible by careful selection of high-Rydberg states as the precursor to autoionization.…”
Section: Rotational State Distributions From Autoionization Of G Rydb...mentioning
confidence: 99%
“…However, in recent applications, this approach has only succeeded in producing molecular ions distributed over at least three final rotational states. 8,9 Indeed, earlier work demonstrated that rotational quantum number changes as large as four quanta are possible in the autoionization of certain Rydberg series, 10,11 upending the simple picture of the Rydberg electron being released without perturbation of the ion-core.…”
Section: Introductionmentioning
confidence: 99%
“…The latter keeps all the benefits of using molecular ions in an ion trap, and it also boasts a larger effective electric field and longer coherence times than the former [18][19][20][21]26], both of which promise a direct increase in the eEDM sensitivity. Previous spectroscopic work [26][27][28][29] shows that we can use similar experimental techniques across both molecular species, including multi-state detection [25,30]. Hence, the molecule switch presents no new immediate experimental complexity, and promises higher eEDM sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Borrowing wisdom and experimental techniques from similar spectroscopic work performed on HfF + [31][32][33][34], ThF [27], and ThF + [26], we (i) perform spectroscopy on the eEDM-sensitive state in ThF + , X 3 ∆ 1 , (Section II) to extract spectroscopic constants of concern, and discuss theoretical calculations of aforementioned spectroscopic constants; and (ii) study the lifetime of the first vibrational excited state in ThF + (Section III) and its implications on the expected coherence time of X 3 ∆ 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopy of the atomic lanthanides is well characterized, 19 but the spectroscopy of the oxides is very much a work in progress. 20,21 SmO, NdO, and their cations have many low-lying electronic states due to their partially filled f-shells and are challenging to explore. Electronic states of NdO + with term energies of up to ~5,000 cm -1 have been determined using pulsed-field ionization zero electron kinetic energy (PFI-ZEKE) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%